Earnings Response Coefficient : CSR Disclosure, Audit Committe and Default Risk - Miftah Kamal Nuriyanto; Annisa Nurbaiti; Wiwin Aminah (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
An investor needs to collect financial information as a matter of consideration in making his economic decision by using earning response coefficient. The value of ERC that appears will be goodnews when the value is raised high and will be badnews when the value of ERC is low. This research aims to test how the influence of CSR Disclosure, Audit Committee and Default Risk to Earnings Response Coefficient. The research was conducted on the basic and chemical industry sectors list on the IDX from 2015 to 2018. By using pusposive sampling technique obtained as many as 23 companies with 4 years observation time obtained amount 92 observations. Outliers performed 11 observations so that the number of observations used was 81 observations with Non-probability sampling. This research uses a descriptive statistical analysis technique and a data panel regression method. Results showed that the CSR Disclosure, Audit Committee, Default Risk simultaneously, has an influence on the earnings response coefficient. Partially, audit committee has a negative affect on the earnings response coefficient. While the CSR Disclosure and Default Risk has no affect on the earnings response coefficient.